THE SPECIFIC FEATURES OF HEART AND VESSELS REMODELING IN PATIENTS WITH CHRONIC HEART FAILURE TREATED WITH LISINOPRIL DURING 6 MONTHS - N. A. Kosheleva; A. P. Rebrov (Столичная издательская компания, 2016)
Background. Being able to attenuate pathological remodeling, ACE inhibitors are considered to be first line medications for chronic heart failure (CHF) treatment.Aim. To study the influence of the 6-month combined therapy with lisinopril on the heart and vessels remodeling in patients with ischemic CHF.Material and Methods. 40 patients with CHF after Q-myocardial infarction were treated with lisinopril (Listril, Dr.Reddy's, India) as a part of complex therapy. Initially and after 6 months of therapy the following findings were evaluated: the 6-minute walk test results, echocardiography parameters, main arteries rigidity, endothelium-dependent and independent vasodilatation, anticoagulant and fibrinolytic function of vascular endothelium, von Willebrand factor (VWF).Results. 6-month treatment with lisinopril showed reduction in CHF functional class in 30 % of patients and increase in left ventricle (LV) stroke volume by 3,8% and LV ejection fraction by 1%. Pulse-wave velocity reduced insignificantly from 10,2 to 9,2 m/sec and augmentation indices of aorta from 31,4% to 29,9% as well as this of brachial artery from -2,6% to -6%. Endothelium-dependent vasodilatation increased from 6,4% to 8,6% and independent vasodilatation - from 13,8% to 16,6%. VWF activity decrease was observed in 40% of CHF patients. Significant changes in anticoagulant and fibrinolytic function of vascular endothelium were not revealed.Conclusion. Lisinopril administration as a part of complex therapy of CHF patients during 6 months resulted in favorable effect on heart and vessels remodeling and was well tolerated.